Radar-Based Tsunami Detection: A Comprehensive Review - Adiprabowo, Tjahjo; Ramdani, Dani; Daud, Pamungkas; Andriana, Andriana; Ali, Erfansyah; Nasrullah, Nanang; Zulkarnain, Zulkarnain (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2024)
A tsunami is a large sea wave caused by an earthquake or underwater landslide. Timely detection of tsunamis is critical to saving lives and minimizing damage to infrastructure. Radar has proven to be an effective tool for tsunami detection. This comprehensive review discusses the use of radar for tsunami detection. The two types of radar discussed are HF (High Frequency) radar and DART (Deep ocean Assessment and Reporting of Tsunamis) radar. HF radar can detect tsunamis from long distances in real-time. However, HF radar is susceptible to electromagnetic interference. The DART radar is specifically designed for deep sea tsunami detection. This radar provides real-time information about tsunami waves. However, the DART radar requires expensive marine infrastructure to install and operate. This review concludes that HF radar and DART radar have their respective advantages and disadvantages. The combination of both types of radar can provide a more comprehensive solution for tsunami detection. Further research is needed to improve the reliability of radar-based tsunami detection systems.